Competency Gap Analysis and Experiential Learning Needs in Student Organization - Nahwa Nur Rofahiyah; Laila Listiana Ulya (Universitas Negeri Semarang, 2026)
Background – Student Organizations (Ormawa) serve a strategic role as a non-formal learning environment to bridge graduate competency gaps. However, competency development efforts within these organizations are frequently ad-hoc and assumption-based. Research Urgency – This study is critical to address the inefficiency of irrelevant intervention programs resulting from a lack of objective diagnostic data in designing learning interventions. Objective – This study aims to map the competency gaps of student organization administrators and prioritize their learning intervention needs. Methods – This research employed an explanatory sequential mixed-methods design, involving 46 administrators of the UNNES Psychology Student Association in a quantitative survey based on McGehee & Thayer’s Training Needs Analysis (TNA) model, which was subsequently deepened through Focus Group Discussions (FGD) with 23 representatives. Findings – The results identified the highest competency gaps in ‘Time Management,’ ‘Innovation,’ and ‘Event Management.’ Qualitative analysis revealed that the root causes of these gaps lay at the organizational level, not merely the individual level. Conclusion – These findings confirm that a diagnostic approach is capable of uncovering the actual needs of administrators, including a strong preference for experiential learning methods as a form of non-financial compensation. Novelty/Contribution – This research contributes by demonstrating the application of the Training Needs Analysis (TNA) framework as a formal diagnostic tool to formulate effective learning intervention designs within a non-formal educational setting.